1977
DOI: 10.1111/j.1600-0722.1977.tb00576.x
|View full text |Cite
|
Sign up to set email alerts
|

Microorganisms in recurrent aphthous ulcerations

Abstract: Qualitative and quantitative examinations of the cultivable bacterial flora in biopsies irom recurrent aphthous ulcerations (RAU), experimental oral ulcerations (EOU), and nonnal oral mucosa (NOM) were carried out under aerobic and continuous anaerobic conditions. An attempt was made to culture yeasts, mycoplasma, and virus from the biopsies of RAU, which were also tested for the presence of herpes virus antigen by the fluoicsceiit atitibody method. The predominant bacteria recovered in RAU were ahcniolytic st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
1

Year Published

1989
1989
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 17 publications
0
7
1
Order By: Relevance
“…However, serum levels of IFN‐ γ which tend to rise in viral infections, are not increased in RAS (Hooks et al , 1979). HSV has not been successfully isolated from lesional material (Donatsky et al , 1977; Rothe et al , 1978), only about a third of RAS patients are HSV seropositive (Ship et al , 1967), and HSV is rarely detected in lesional tissue by PCR (Studd et al , 1991).…”
Section: Microbial Aspects Of Rasmentioning
confidence: 99%
“…However, serum levels of IFN‐ γ which tend to rise in viral infections, are not increased in RAS (Hooks et al , 1979). HSV has not been successfully isolated from lesional material (Donatsky et al , 1977; Rothe et al , 1978), only about a third of RAS patients are HSV seropositive (Ship et al , 1967), and HSV is rarely detected in lesional tissue by PCR (Studd et al , 1991).…”
Section: Microbial Aspects Of Rasmentioning
confidence: 99%
“…A hypothesis has been suggested that aphthous ulcers are caused by reactivation of a latent virus, probably within the herpes family (16). Approximately one‐third of all RAS patients have a positive anti‐herpes simplex virus (HSV) antibody titer (17), however, HSV antigen has not been found in smears and biopsy specimens from RAS patients (18). Viruses such as herpes simplex, varicella zoster (19), adenoviruses, and others (20), as well as bacteria, mainly the L‐form streptococcal bacteria— Streptococcus sanguis and Streptococcus mitis [isolated by Graykowski et al in 1966 (21) from the oral ulcers of RAS]—could have a possible link to RAS.…”
Section: Predisposing Factorsmentioning
confidence: 99%
“…In contrast to previous studies, in which the microbiota was sampled in the ulcerative lesion (12, 13) we focused on the microbiota of the non-inflamed buccal mucosa in patients with RAS. Patients with or without ulcerations at the time of sampling were included, to determine whether the microbiota changes in relation to disease activity.…”
mentioning
confidence: 99%